EDUKASI PENANGANAN PENYU HIJAU (Chelonia mydas) TERLUKA AKIBAT PENANGKAPAN LIAR OKNUM MASYARAKAT KELURAHAN SUPRAU - Mohammad Sayuti; Ferliana Widasari; Ahmad Junaidi; Agung Setia Abadi; Achmad Sofian (Buletin SWIMP, 2021)
The number of turtle populations from year to year has decreased. One of the causes is the arrests made by the community for consumption purposes. On April 29, 2021, a green turtle was eaten by the Directorate of Polair, Sorong City, with an injured condition that will be used as food for consumption. The purpose of this activity is to educate the public on the handling of injured turtles and socialize related to turtle conservation. The method of turtle handling activities is direct daily care with medication and turtle feeding programs, while socialization activities are carried out with mini workshops attended by representatives of the Marine and Fisheries Resources Supervisor,  Sorong Marine and Fisheries Polytechnic, Directorate of Polair Sorong City, West Papua Natural Resources Conservation Center, Sorong District Court, Sailing Science Education and Training Center, Sorong City Fisheries Service, Papua Turtle Foundation, Conservation International (CI) and Nusantara Nature Conservation Foundation and public figure. The results of the activities for handling injured turtles, healthy turtles returned with dry wounds so that the turtles could be released into the wild. The socialization activity went smoothly with increasing understanding regarding the importance of turtle conservation by the community by signing a Memorandum of Understanding related to turtle conservation.